Exploring the Role of Overall Survival in Chemotherapy Protocol: A Literatur Review: Telaah Pustaka Penilaian Overall Survival Sebagai Parameter Klinis Tata Terapi Kanker - Pratiwi, Selma Septi; Khamdun, Ibnu; Fitrianasari, Resma Dwi Putri; Vaira, Tischa; Riska, R; Santoso, Setiyo Budi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
Overall survival (OS) assesses the patient's survival rate after undergoing therapy. The evaluation of OS becomes a reliable clinical endpoint for assessing the malignancy response to chemotherapy intervention. Here in, we review a number of publications on PCR data in various chemotherapy protocols for different types of cancer. The literature review involves nine scientific articles that meet the inclusion criteria provided by the PubMed database. Our findings present the performance of chemotherapy protocols with the highest OS values for each type of cancer, including: Non-Small Cell Lung Cancer Metastasis (Durvalumab plus Tremelimumab-31.2), Non-Metastatic Non-Small Cell Lung Cancer (Nivolumab-30.8), Small Cell Lung Cancer (Carboplatin and Etoposide-13.2), Breast Cancer (Ribociclib plus Fulvestrant-67.6), Metastatic Breast Cancer (Olaparib-18.9), Metastatic Colorectal Cancer (Trifluridine/tipiracil-13.1), Liver Cancer (SBRT 44.1). This article reviews a number of publications on PCR data in various chemotherapy protocols for different types of cancer.